Iron toxicity symptoms in yams (Dioscorea spp.) grown in water culture - Shiwachi, H.; Kikuno, H.; Okonkwo, C.C.; Asiedu, Robert (Wiley, 2006)
Growth of varieties of Dioscorea alata and D. rotundata were stunted when they were grown in nutrient solutions containing 5 to 60 mg l−1 Fe. In D. alata variety TDa 95/00361, plants grown in 60 mg l−1 Fe solution exhibited reductions of 29–65% in plant height, leaf length and width, number of leaves, stems and roots, and root length compared to the control. The corresponding values for D. rotundata variety TDr 89/02565 were 34–59%. Tuber weight in D. rotundata variety TDr 89/02565 was increased by the iron treatments but the foliar symptoms of iron toxicity reported for other crops were not observed.